AGTRAP Is a Prognostic Biomarker Correlated With Immune Infiltration in Hepatocellular Carcinoma - Liu, Shanshan; Zhao, Wei; Li, Xuemei; Zhang, La; Gao, Yu; Peng, Qiling; Du, Chengyou; Jiang, Ning (Frontiers in Oncology, 2021)
Backgrounds: Recently it has been reported that Angiotensin II receptor-associated protein (AGTRAP) plays a substantial role in tumor progression. Nevertheless, it remains unrecognized about the possible valuation of AGTRAP in hepatocellular carcinoma (HCC). Methods: MERAV, CCLE, HPA, and HCCDB databases were used to analyze the expression of AGTRAP between HCC tissues and normal liver tissues or adjacent tissues. Kaplan-Meier plotter and UALCAN were applied to validate the prognosis and diagnosis value of AGTRAP. LinkedOmics and cBioPortal were used to explore co-expressed genes of AGTRAP in HCC. To further understand the potential mechanism of AGTRAP in HCC, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment pathway analyses were performed by R software, protein-protein interaction (PPI) network was established by STRING database, and the immune infiltration and T cell exhaustion related to AGTRAP were explored by Timer and GEPIA. In addition, immunohistochemistry (IHC) was applied to detect the expression of AGTRAP protein in HCC tissues and matched adjacent tissues from clinical specimens. Results: This study indicated that the levels of AGTRAP mRNA and protein in HCC tissues were higher than those in normal liver tissues and adjacent tissues, and higher mRNA level of AGTRAP was relevant to higher histological grade and poor overall survival (OS) time of HCC patients. The area under the receiver operating characteristic curve (AUC) of AGTRAP was 0.856, suggesting a diagnostic marker in HCC. Besides, the alteration rate of AGTRAP in HCC is 8%, AGTRAP was involved in HCC probably through NF-κB and MAPK signaling pathway. Furthermore, AGTRAP had a positive correlation with the infiltration of CD8+ T Cells, CD4+ T Cells, B Cells, macrophages, dendritic cells, and neutrophils, and the level of AGTRAP was also significantly correlated with T cell exhaustion biomarkers. Consistently, the results of IHC confirmed that the protein level of AGTRAP was higher in HCC tissues than that in matched adjacent tissues. Conclusion: Data mining could effectively identify the clinical value of AGTRAP and its correlation to immune infiltration in HCC. AGTRAP could be served as a potential biomarker of prognostic, diagnosis, and even immunotherapy target for HCC.